3D printed extended-release hydrochlorothiazide tablets - Tasevska, Teodora; Adamov, Ivana; Geškovski, Nikola; Ibrić, Svetlana; Gorachinova, Katerina; Simonoska crcarevska, Maja (Elsevier BV, 2025)
In this study 3D printed tablets (printlets) with extended release of hydrochlorothiazide (HHT) as model active ingredient were designed and developed. Four formulations, F0.1SSE, F1SSE, F0.1DLP and F1DLP, have been manufactured and characterized, using non-typical semi-solid extrusion (SSE) with UV light solidification and digital light processing (DLP) techniques. Obtained rheological studies pointed out to F1SSE and F1DLP as more suitable for SSE and DLP printing, respectively. Photopolymerization process between photopolymer (PEGDA) and photoinitiator (DPPO; 0.1% and 1%) was investigated using FTIR, with PCA modeling utilized to analyze spectral variations over time and estimate crosslinking kinetics. SSE printlets averaged ∼6.5 mm in diameter, ∼3 mm in height and ∼110 mg in mass, while DLP printlets averaged ∼8.5 mm in diameter, ∼2.5 mm in height, with masses of ∼170 mg (F0.1DLP) and ∼220 mg (F1DLP). All four formulations complied to the requirements of European pharmacopeia for uniformity of dosage units of single dose preparations. In vitro release studies indicated extended-release profiles in both 0.1M Hydrochloric acid (HCl) and phosphate buffer pH 6.8 for SSE and DLP printlets. The release kinetics of HHT from the printlets were modeled to fit First order, Higuchi, Korsmeyer-Peppas and Hixson-Crowell equations and the most probable ones were determined based on the R2 values and Akaike information criterion. FTIR and Raman spectroscopic analyses of printlets confirmed the presence of characteristic peaks from both, HHT and excipients, as well as modifications in bonds due to the photopolymeric reaction.